QUBLA ARAL BOYÍ AYMAǴÍNDAǴÍ TÁBIYIY OBYEKTLERDIŃ ELEMENTLIK QURAMÍN KOMPLEKS ÚYRENIW - Jumamuratov, A.; Jumamuratov, M.A.; Sdıkov, I.M. (SCIENCE and SOCIETY, 2024)
The use of the neutron activation analysis method is of great importance in determining their chemical composition and a comprehensive study of natural objects of the Southern Aral Sea region. About 30-35 chemical elements were identified in the ecological objects of the Southern Aral Sea region and it was established that the natural balance in them was disturbed and the elemental composition of the soil was changed.